A gamified digital framework in higher education: impact on learning and motivation - Carrión Candel, Elena; de-la-Peña, Cristina; Chaves Yuste, Beatriz (Turkish Online Journal of Distance Education-TOJDE, 2025)
The use of gamified digital tools has become a key and dynamic component in the work of educators, playing a crucial role in shaping various educational tasks. These tools offer a more playful, effective, and interactive learning experience aimed at increasing student motivation and providing immediate feedback. Based on these principles, this study proposes to analyze the improvement in student learning and motivation following the application of a didactic experience using gamified digital resources (Nearpod, Genially, Educaplay, Breakout, and Quizizz) in an online university classroom. The implementation was carried out over a five-month period with pre-service teachers (n=147) from the Bachelor’s Degree in Early Childhood and Primary Education and the Master’s Degree in Secondary Education and Teacher Training at a private Spanish university. A pre-experimental design with pre- and post-intervention measurements was employed. The research results demonstrate that the use of these gamified digital resources enhances students’ perceptions of music learning in an online university environment. The findings reveal a positive impact across all evaluated areas following the didactic intervention, with significant improvements ranging from perceptible to moderate in university students’ perceptions of learning and motivation. Therefore, the study’s findings have practical educational implications, highlighting the appropriateness of using these digital resources not only in music courses but also in other subjects within the curriculum, promoting active learning in the classroom.
Keywords: gamification; higher education; digital tools; online learning; motivation; music education